(untitled) (Scientific journal of the Fergana State University, 2024)
Distance learning of a foreign language is becoming more and more popular in modern education. This article examines the effectiveness of the teaching method and defines the criteria for its success. Research results show that distance learning can be effective under certain conditions, such as the use of interactive methods, individualized approaches to students, and continuous monitoring of progress. This article provides valuable recommendations for teachers and students who want to succeed in learning a foreign language through distance technology. This article provides examples and analyzes online platforms designed for establishing a foreign language in foreign countries and Uzbekistan.